Ekowisata : Utopia dalam Keberlanjutan - Seliari, Tutun; Ikaputra, Ikaputra (Jurnal Ilmiah Pariwisata, 2021)
Ecotourism is a form of tourism activity that is oriented towards the balance of the ecosystem. Ecotourism demands environmental development and changing community needs. Based on several cases, ecotourism has an impact on the environment. Reality shows that ecotourism activities can provide economic incentives for conservation but also have the potential to affect the quality of environmental degradation if not managed properly. The problem raised in this paper is how to realize the concept of ecotourism and environmental balance so that it does not only become a utopia in sustainability. The method used in this paper is a literature review or literature review by reviewing writings related to ecotourism and sustainability. The result obtained is that the natural environment becomes the main basis as an attraction in ecotourism. Ecotourism that is growing rapidly needs to be anticipated so that it does not exceed the limit resulting in natural and cultural degradation. A strategy is needed so that ecotourism does not cause environmental damage, among others, by utilizing local initiatives related to conservation and paying attention to aspects of the area's carrying capacity to support sustainability efforts. Keywords: Ecology, Ecotourism, Sustainable Development, Local Initiatives